Achondrogenesis type I. A familial subvariant?. Issue 7 (July 1976) - Lauder, I; Ellis, H A; Ashcroft, T; Burridge, A
Abstract : The clinical, pathological, and radiological features of 2 male sibs with a severe and lethal form of micromelic dwarfism are desribed. The family also includes 2 normal sibs. The histological and radiological appearances suggested a diagnosis of achondrogenesis type I, but the markedly deficient ossification of the skull and the presence of intrauterine rib fractures were atypical. These changes have been observed in two other families with 2 or more infants with suspected achondrogenesis, raising the possibility that these familial cases may be a subvariant of achondrogesis or even a distinct disease entity. The disease appears to be inherited as an autosomal recessive and death occurs shortly after birth because of severe pulmonary hypoplasia.